Review article: the economic impact of the irritable bowel syndrome - Canavan, C.; West, J.; Card, T. (Alimentary pharmacology & therapeutics, 2014)
Summary Background Irritable bowel syndrome (IBS) is a chronic functional disorder of the gastrointestinal system affecting a large number of people worldwide. Whilst it has no attributable mortality, it has substantial impact on patients' quality of life (QoL) and is associated with considerable healthcare resource use. Aim To review the economic impact of IBS, firstly on the individual, secondly on healthcare systems internationally and thirdly to society. Methods Appropriate databases were searched for relevant papers using the terms: Irritable Bowel Syndrome; IBS; irritable colon; functional bowel/colonic disease; economics; health care/service costs; health expenditure/resources; health care/service utilisation; productivity. Results Irritable bowel syndrome impacts most substantially on patients' work and social life. Reduction in QoL is such that on average patients would sacrifice between 10 and 15 years of their remaining life expectancy for an immediate cure. Between 15% and 43% of patients pay for remedies. No studies quantify loss of earnings related to IBS. Direct care costs are substantial; 48% of patients incur some costs in any year with annual international estimates per patient of: USA $742–$7547, UK £90–£316, France €567–€862, Canada $259, Germany €791, Norway NOK 2098 (€262) and Iran $92. Minimising extensive diagnostic investigations could generate savings and has been shown as not detrimental to patients. Cost to industry internationally through absenteeism and presenteeism related to IBS is estimated between £400 and £900 per patient annually. Conclusions Irritable bowel syndrome is associated with substantial costs to patients, healthcare systems and society. Considerable benefit could be obtained from effective interventions.